Pratiques d’amateurs en animation de communautés sur Facebook dans le domaine de la vitiviniculture - Marie-Caroline Heïd; Catherine De Lavergne (Communiquer)
Activities related to the animation of online community links for professional purposes are diffusing into the sphere of small family businesses. This article analyzes beginner practises in community management of small viticulture businesses on Facebook. Our case study focuses on four winegrowers of the AOC Languedoc in France, who are still novices in community management. We investigate identity propositions offered by winegrowers on fan pages in support of their respective organizations. We try to understand underlying processes that contribute, through the animation of fan pages, in building up their respective communities. Subsequently, we analyze prescriptions given to users in the interface’s design, as well as in the support information provided. Finally, we conduct interviews with the winegrowers, and link our observations with their own specific objectives and challenges. In this way, we analyze the effects of these activities on the communication dynamics that affect the structuring of their organizations.